A future employment trend - the urban farmer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The principal aim of urban agriculture is the provision of fresh produce for city markets. These days one possible option for victims of the economic crisis can be market gardening. However, because market gardening often develops somewhat...